2017
DOI: 10.17796/1053-4628-41.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Temporomandibular Dysfunction and its Association with Malocclusion in Children: An Epidemiologic Study

Abstract: In this study, many subjects with TMD had malocclusions. Early treatment may be important in the prevention of severe TMD. Significant associations were found between different signs, and TMD was associated with posterior crossbite, anterior open bite, Angle Class II and III malocclusions, and extreme maxillary overjet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 2 publications
3
30
2
6
Order By: Relevance
“…Although excessive loading may stress the masticatory muscles, in this study the association between excessive overjet and TMD was not significant in the multiple regression analysis. In a bivariate analysis, TMD symptoms have a statistically significant relationship with excessive overjet as well as myofascial pain and disc displacement with reduction.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Although excessive loading may stress the masticatory muscles, in this study the association between excessive overjet and TMD was not significant in the multiple regression analysis. In a bivariate analysis, TMD symptoms have a statistically significant relationship with excessive overjet as well as myofascial pain and disc displacement with reduction.…”
Section: Discussioncontrasting
confidence: 71%
“…The relation between Angle molar relationship and TMD is controversial on the literature. Thilander (2002) evaluated 4724 children and adolescents (5‐17 years old) and Bilgiç (2017) examined 923 children (7‐12 years old) found a significant association between Class III and TMD. Other authors found no evidence of this relationship .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMDs were associated most commonly with posterior crossbite, anterior open bite, Angle Class II and III malocclusions, and maxillary overjet. [27] Although this was not statistically significant, further investigations can divulge conclusive information on the presence or absence of a relationship between TMDs and orthodontic therapy. The other factors that were added into the questionnaire included trauma to chin or jaw and previous history of treatment for TMDs.…”
Section: Discussionmentioning
confidence: 89%
“…Twenty-six percent of the students reported the presence of different symptoms of TMDs. A study by Bilgiç and Gelgör[27] revealed that in children aged between 7 and 12 years many subjects with TMD had malocclusions. TMDs were associated most commonly with posterior crossbite, anterior open bite, Angle Class II and III malocclusions, and maxillary overjet.…”
Section: Discussionmentioning
confidence: 99%